2020
DOI: 10.3390/ma13102383
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies on the Centrifugal MQL-CCA Method of Applying Coolant during the Internal Cylindrical Grinding Process

Abstract: This paper presents the results of experimental research concerning the possibility of supporting the cooling function during internal cylindrical grinding using the minimum quantity lubrication (MQL) method by additional delivery of a compressed cooled air (CCL) stream. The article presents a description of a hybrid method of cooling and lubrication of the grinding zone integrating centrifugal (through a grinding wheel) lubrication with the minimum quantity of lubricant and cooling with a compressed cooled ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…The results of numerical simulations [126] and experimental research [127] have shown that the developed hybrid method allows for about 2.7 times longer wheel life in comparison with the results obtained under flooded cooling or centrifugal MQL conditions. The wheel life was as much as 8 times longer in comparison with the wheel life under SSP only delivering or dry grinding conditions.…”
Section: Centrifugal Mql and Delivery Of Compressed Cold Airmentioning
confidence: 88%
See 4 more Smart Citations
“…The results of numerical simulations [126] and experimental research [127] have shown that the developed hybrid method allows for about 2.7 times longer wheel life in comparison with the results obtained under flooded cooling or centrifugal MQL conditions. The wheel life was as much as 8 times longer in comparison with the wheel life under SSP only delivering or dry grinding conditions.…”
Section: Centrifugal Mql and Delivery Of Compressed Cold Airmentioning
confidence: 88%
“…They were the motivation to undertake work aimed at applying the CAOM method also in the process of internal cylindrical grinding characterized by limited space in the contact zone of the grinding wheel with the workpiece. This is how the method was developed in which a patented centrifugal air-oil aerosol delivering through the grinding wheel [124] was combined while simultaneous incorporating the CAG nozzle into the system [125][126][127].…”
Section: Centrifugal Mql and Delivery Of Compressed Cold Airmentioning
confidence: 99%
See 3 more Smart Citations